Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1007/bf01536771
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of secretory IgA and secretory component of immunoglobulins in small intestine of rats treated withSaccharomyces boulardii

Abstract: Saccharomyces boulardii (S.b.) is largely used in Western European countries for the treatment of acute infectious enteritis and antibiotic-induced gastrointestinal disorders. To study the mechanisms of the protective effect of S.b. against enteral pathogen infection, we assessed the response of the intestinal secretion of secretory IgA (s-IgA) and of the secretory component of immunoglobulins (SC) to oral administration of high doses (0.5 mg/g body weight, three times per day) of S.b. cells in growing rats. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
137
3
9

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(155 citation statements)
references
References 27 publications
6
137
3
9
Order By: Relevance
“…Many mechanisms of action have been proposed to explain yeast probiotic protection against bacterial infection, such as modulating the immune system (Buts et al, 1990;Rodrigues et al, 2000), degrading Clostridium difficile toxins A and B and their respective receptors on colonic mucosa (Castagliuolo et al, 1999;Qamar et al, 2001), inhibiting cholera toxin action (Czerucka et al, 1994;Brandão et al, 1998) and modulating the transduction pathway when activated by enteropathogenic bacteria (Czerucka et al, 2000;Dahan et al, 2003;Martins et al, 2010Martins et al, , 2011. Another frequently cited mechanism for probiotic action is the production of diffusible antagonistic compounds inhibiting pathogenic bacterial growth.…”
Section: Introductionmentioning
confidence: 99%
“…Many mechanisms of action have been proposed to explain yeast probiotic protection against bacterial infection, such as modulating the immune system (Buts et al, 1990;Rodrigues et al, 2000), degrading Clostridium difficile toxins A and B and their respective receptors on colonic mucosa (Castagliuolo et al, 1999;Qamar et al, 2001), inhibiting cholera toxin action (Czerucka et al, 1994;Brandão et al, 1998) and modulating the transduction pathway when activated by enteropathogenic bacteria (Czerucka et al, 2000;Dahan et al, 2003;Martins et al, 2010Martins et al, , 2011. Another frequently cited mechanism for probiotic action is the production of diffusible antagonistic compounds inhibiting pathogenic bacterial growth.…”
Section: Introductionmentioning
confidence: 99%
“…The former possibility has not yet been studied until now, while the latter has been investigated in several animal and human studies in the past (Buts et al, 1986;1990;1994).…”
Section: Discussionmentioning
confidence: 99%
“…Clarithromycin and S. boulardii were dissolved in saline. The dose selection of the test drugs were according to the previous in vivo rat studies (Buts et al, 1990;Kim et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that fSC is an 80 kDa glycoprotein, consisting of a single polypeptide chain largely glycosilated (20%) (19). There is little information about the role of fSC in secretions, but some workers suggest that it may have a protective role against diarrhea (4,15). Recently, using immunogold labeling, we showed the ability of fSC to interact with CFA I and CFA II (CS1 and CS3) fimbrial adhesins (25).…”
Section: Introductionmentioning
confidence: 99%